EXAMINE ANTIBACTERIA ACTIVITY OF COMMERCIAL FERMENTED DAIRY PRODUCTS AGAINST PATHOGENS BACTERIA - Nur Khikmah (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2015)
The aim of this research was to examine antibacteria activity of commercial fermented dairy products against pathogens bacteria. The antibacteria activity was determined using the well diffusion method. The presence of antibacteria activity were shown by clear zone which formed around well containing fermented dairy products. The results show that yakult and probiotics yoghurt able to inhibit the growth of pathogens bacteria. The most sensitive pathogen bacteria to fermented dairy products was Salmonella thypii. Inhibition yakult and probiotics yoghurt against gram negative bacteria were greater than gram positive bacteria. Yakult containing Lactobacillus casei strain shirota was able to inhibit all pathogens bacteria, such as Salmonella thypii, Escherichia coli, Bacillus cereus, and Staphylococcus aureus.